FRI0142 High Prevalence of Depression in Patients with Rheumatoid Arthritis - Data from The Large Cross-Sectional Vadera II Study. (15th July 2016) - Englbrecht, M.; Alten, R.; Aringer, M.; Baerwald, C.G.; Burkhardt, H.; Eby, N.; Flacke, J.-P.; Fliedner, G.; Gauger, B.; Henkemeier, U.; Hofmann, M.W.; Kleinert, S.; et al.
Abstract : Background: Depression is a frequent if not the most frequent comorbidity in patients with rheumatoid arthritis (RA) [1]. Objectives: To investigate the prevalence of depressive symptoms in RA patients in a standardized manner in the clinical setting using two previously validated questionnaires and to test for clinical characteristics associated with depressive symptomatology. Methods: To assess depressive symptoms the validated 9 item version of the patient health questionnaire (PHQ-9) and the Beck-Depression Inventory II (BDI-II) were used. In addition, demographic background, RA disease activity according to DAS28, RA disease symptoms according to the RAID questionnaire, comorbidities and anti-rheumatic as well as anti-depressive treatment were recorded. Cut-off values for depressive symptomatology were PHQ-9≥5 or BDI-II≥14 (ie mild depressive symptoms or worse). Numbers for frequency of depressive symptomatology were derived by frequency analysis while factors independently associated to depressive symptomatology were investigated by odds ratios and 95% confidence intervals using multiple logistic regression analyses. IRB approval was obtained and all patients completed an informed-consent form prior to participation. Results: In 1004 RA-patients (75.1% female, mean age: 61.0±12.9 years, mean disease duration: 12.2±9.9 years, DAS28(ESR): 2.5±1.2) the prevalence of depressive symptoms was 55.4% according to predefined cut-offs (more restrictive cut-offs indicating moderate depressive symptoms at least, i.e. PHQ-9 ≥10 or BDI-II ≥20 still classified 22.8% of our patients as being depressed). Characteristics independently associated with depressive symptomatology were: age >60 years (OR=0.62 (95%CI: 0.46, 0.83)), DAS28(ESR) ≥3.2 (OR=1.52 (95%CI: 1.03, 2.27)), RAID score >5 (OR=8.28 (95%CI: 5.36, 12.80)) and presence of chronic pain (OR=2.55 (95%CI: 1.42, 4.57)). Only 11.7% of patients classified as having depressive symptoms received anti-depressive drug therapy. Conclusions: More than half of RA patients showed symptoms of depression, which were associated with age, RA disease activity, a high impact of RA symptoms on the life of patients and the presence of chronic pain. However, only a small number of RA patients were receiving appropriate anti-depressive therapy. These findings strongly suggest the need for better assessment of depression in routine rheumatologic care. References: Dougados M, Soubrier M, Antunez A, et al. Prevalence of comorbidities in rheumatoid arthritis and evaluation of their monitoring: results of an international, cross-sectional study (COMORA). Ann Rheum Dis. 2013. Disclosure of Interest: M. Englbrecht Grant/research support from: Research grant for VADERA: Chugai Pharma Europe Ltd. and Roche Pharma AG, R. Alten Grant/research support from: Roche, Chugai, Speakers bureau: Roche, Chugai, M. Aringer Consultant for: Roche, Chugai, Speakers bureau: Roche, Chugai, C. Baerwald: None declared, H. Burkhardt Grant/research support from: Roche, Chugai, Consultant for: Roche, Chugai, N. Eby Consultant for: Fees from Roche Pharma AG for statistical analysis and manuscript preparation during the conduct of the study, J.-P. Flacke Employee of: Roche Pharma AG, G. Fliedner Consultant for: Roche, Chugai, Paid instructor for: Roche, Chugai, B. Gauger Employee of: Roche Pharma AG, U. Henkemeier: None declared, M. Hofmann Employee of: Chugai Pharma Europe Ltd., S. Kleinert Speakers bureau: Abbvie, Chugai, Pfizer, Roche, UCB, Medac, C. Kneitz Grant/research support from: Pfizer, Consultant for: AbbVie, Janssen, Pfizer, Berlin Chemie, Chugai, Roche, Speakers bureau: AbbVie, Janssen, Pfizer, Berlin Chemie, Chugai, Celgenge, Novartis, Roche, MSD, UCB, K. Krüger Employee of: Chugai Pharma Europe Ltd., R. Lüthje: None declared, C. Pohl: None declared, G. Schett Grant/research support from: Research grant for VADERA: Chugai Pharma Europe Ltd. and Roche Pharma AG, M. Schmalzing Consultant for: Chugai, Novartis, Roche, Speakers bureau: AbbVie, Actelion, BMS, Chugai, Genzyme, Janssen-Cilag, Novartis, Pfizer, Roche, UCB, A.-K. Tausche: None declared, H. P. Tony Grant/research support from: Roche Pharma AG, Consultant for: Abbvie, BMS, Chugai, Janssen, Lilly, Novartis, Roche, UCB, Speakers bureau: Abbvie, BMS, Chugai, Janssen, Lilly, Novartis, Roche, UCB, J. Wendler Consultant for: Roche, Chugai, Speakers bureau: Roche, Chugai